2011
DOI: 10.1108/02637471111154809
|View full text |Cite
|
Sign up to set email alerts
|

Housing affordability in Australia for first home buyers on moderate incomes

Abstract: PurposeThis paper seeks to examine the opportunity for home ownership by first‐time buyers who are in occupations defined in the UK literature as key workers within four state capitals in Australia: Adelaide, Melbourne, Sydney, and Brisbane. Many of these workers are moderate or average income earners who deliver essential community services such as health, social services, education, safety and emergency services. This paper aims to explore access to home ownership for these workers for 2001 and 2009, a perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 8 publications
3
10
0
Order By: Relevance
“…It can be observed the FHOG scheme was positive and statistically significant at the 5 per cent level, indicating increases in the FHOG scheme value would increase the level of housing affordability among first-time buyers. This result supports the findings of Kupke & Rossini (2011) and the visual presentation in Figure 1 in which a strong government incentive to purchase substantially improved the level of housing affordability among first-time buyers. In other words, it has been demonstrated that the FHOG scheme is an effective housing scheme to increase housing affordability.…”
Section: The Fhog Scheme and Housing Affordabilitysupporting
confidence: 93%
See 1 more Smart Citation
“…It can be observed the FHOG scheme was positive and statistically significant at the 5 per cent level, indicating increases in the FHOG scheme value would increase the level of housing affordability among first-time buyers. This result supports the findings of Kupke & Rossini (2011) and the visual presentation in Figure 1 in which a strong government incentive to purchase substantially improved the level of housing affordability among first-time buyers. In other words, it has been demonstrated that the FHOG scheme is an effective housing scheme to increase housing affordability.…”
Section: The Fhog Scheme and Housing Affordabilitysupporting
confidence: 93%
“…Guest (2005) concluded that the FHOG scheme does not necessarily imply an increase in housing demand and prices. On the other hand, Kupke & Rossini (2011) argued that government subsidies assisted firsttime buyers to gain access to housing, although the initial gains from the subsidies disappeared into the subsequent larger mortgage loans. Overall, these studies have enriched an understanding about the impacts of the FHOG scheme on housing prices, although there has been relatively little attention placed on the critical relationship between the FHOG scheme and housing price volatility.…”
Section: The Fhog Scheme In Australia and Housing Affordability For Fmentioning
confidence: 98%
“…Meanwhile, the dual-income households between the working spouses encouraged the housing affordability (Scalon&Whitehead, 2004). For instance, a research by Kupke & Rossini, (2011) found the homeownership is increasingly difficult in cities such as Adelaide, Melbourne and Brisbane for the single income household. This phenomenon not only happened in Australia cities, but single income household mainly in Germany's cities also encountered the complications of housing affordability to the extent of reducing the homeownership rate in the country (Bentzien et al, 2012).…”
Section: Socioeconomic Factorsmentioning
confidence: 99%
“…The household expenditure included several costs in life survivals such as foods, apparels, wellness, educations, investments in human capital (Kutty, 2005), utility payments (Bentzinger& Cook, 2012) and transportation costs (Kupke & Rossini, 2011) are the essences in daily household expenditures. Although each household needed the non-housing expenditures in life, the household expenditures and the consumed priorities differ accordingly.…”
Section: Socioeconomic Factorsmentioning
confidence: 99%
“…Home ownership transition is not only connected to marriage and childbearing, but also to socioeconomic circumstances such as employment status and income, but also parental resources and higher education. In addition, not only life course, but contextual factors play a large role in entering home ownership, including pricing and political framework of the housing market at the time (Kupke & Rossini, 2011;Mulder & Wagner, 1998). In Australia, the Australian Bureau of Statistics has reported a decrease in home ownership rates in people aged 25-34 (Australian Bureau of Statistics, 2004;Flood & Baker, 2010).…”
Section: Home Ownership Across the Life Coursementioning
confidence: 99%